Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan Manufaktur Yang Terdaftar Di Bei Periode Tahun 2016-2020 - Hadli Hadli; Sri Ermeila; Asma Mario (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
In the face of technological advancements and innovations as well as intense competition between companies, companies are encouraging companies to change their habits in managing their businesses, which were previously based on labor towards businesses with the main characteristics of science. The management of all company resources cannot be separated from the intervention of human resources in it. However, there are still many companies in Indonesia that have not managed Intellectual Capital optimally. The research was conducted to show the effect of Intellectual Capital on financial performance as measured by Return On Equity . The data that has been obtained is then processed by multiple linear regression analysis and tested on hypotheses between research variables, either partially or simultaneously in order to know the effect given. The data management used SPSS version 25. The results showed that simultaneously VACE, VAHC and STVA had a significant positive effect, but partially only the STVA variable had no effect on financial performance (ROE).